2017
DOI: 10.3390/ma10070809
|View full text |Cite
|
Sign up to set email alerts
|

Processing Conditions, Thermal and Mechanical Responses of Stretchable Poly (Lactic Acid)/Poly (Butylene Succinate) Films

Abstract: Poly (lactic acid) (PLA) and poly (butylene succinate) (PBS) based films containing two different plasticizers [Acetyl Tributyl Citrate (ATBC) and isosorbide diester (ISE)] at three different contents (15 wt %, 20 wt % and 30 wt %) were produced by extrusion method. Thermal, morphological, mechanical and wettability behavior of produced materials was investigated as a function of plasticizer content. Filmature parameters were also adjusted and optimized for different formulations, in order to obtain similar th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…It is also worthy to mention that the PLA piece containing 20 wt% OLA showed a decrease in impact strength in comparison with the other OLA-containing PLA pieces, thus suggesting certain OLA saturation in the PLA matrix. In this regard, Fortunati et al [56] reported the use of isosorbide diester (ISE) as plasticizer for PLA. It was observed plasticizer saturation at 20 wt% ISE and this was attributed to a limitation of T g decrement.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worthy to mention that the PLA piece containing 20 wt% OLA showed a decrease in impact strength in comparison with the other OLA-containing PLA pieces, thus suggesting certain OLA saturation in the PLA matrix. In this regard, Fortunati et al [56] reported the use of isosorbide diester (ISE) as plasticizer for PLA. It was observed plasticizer saturation at 20 wt% ISE and this was attributed to a limitation of T g decrement.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(butylene succinate) (PBS), a linear aliphatic polyester produced from 1,4‐butanediol and succinic acid via 2 steps of polycondensation, is a semicrystalline polymer . Poly(butylene succinate) has high impact toughness, good flexibility and chemical resistance, and biodegradability in a few weeks . These characteristics enable the use of PBS in biomedical products, packaging, films, and mulch.…”
Section: Introductionmentioning
confidence: 99%
“…polylactic acid (PLA), poly(caprolactone) (PCL), poly(butylene adipate terephthalate) (PBAT), polyhydroxy alkanoates (PHAs) etc.) has received tremendous interest as alternative substitution for petroleum-based polymers towards a wide variety of applications because of the stringent environmental legislations [3,[6][7][8] in place in several countries. This is owing to their unique features, such as eco-friendliness, biocompatibility and ease of processability.…”
mentioning
confidence: 99%
“…For instance, when PLLA content is higher than 90% it tends to be highly crystalline, while melting temperature (Tm) and glass transition temperature (Tg) decrease on decreasing PLLA content. Table 1 presents the main physical properties of PLA-based polymers [3,[6][7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation